The effect of abdominal stretching on pain intensity in adolescent girl for managing dysmenorrhea at SMAN 1 Penawartama, Tulang Bawang Regency, Lampung Province, 2024 - Nuratik, Neng Dini; Nurhayati, Fitri; Rosyeni, Yeni; Roswendi, Achmad Setya (Institute of Computer Science (IOCS), 2025)
Dysmenorrhea is a common complaint frequently experienced by adolescent girls, which may negatively impact daily activities and quality of life. This study aims to determine the effect of abdominal stretching on menstrual pain intensity in adolescent girls. A quasi-experimental method was employed with a pretest-posttest design without a control group. The study population consisted of 88 students from grades X and XI at SMAN 1 Penawartama, with 42 respondents selected using purposive sampling. Data were collected through observation and interviews using a numerical pain scale. The findings revealed that the average pain intensity before abdominal stretching was 3.00, which decreased to 1.00 after the intervention. The Wilcoxon test produced a p-value of 0.000, indicating a significant effect of abdominal stretching in reducing menstrual pain. These results suggest that abdominal stretching can be a practical, non-pharmacological alternative therapy that is easily applied independently by adolescents. The study recommends the incorporation of abdominal stretching exercises in school physical education curricula or adolescent reproductive health programs.